Análise da relação entre papéis gerenciais e dominâncias cerebrais de ministros evangélicos - Goes, Renato César de Mesquita (2018)
The evangelical religious organizations have acquired a great representativeness over the 21st century’s recent decades in the Brazilian religious segment, adopting, in the same period, ways of more marketing organization. These changes have also resulted in the adoption of managerial models more appropriate to business practice, as well as the requirement of more competent leaders and managers. Hence, a few researches have been realized in order to identify cerebral skills, cognitive styles and/or psychological types which influence and cause certain behaviors and attitudes, making possible the development of competencies. Considering this context and the lack of researches which approach managerial competence and brain dominance in religious organizations, this thesis aims to analyze the relationship between the managerial roles assumed by evangelical ministers and their brain dominances. In order to fulfill this objective, a descriptive research with a quantitative approach has been realized, by applying a questionnaire to evangelical ministers. The data relating to management and brain dominances of the ministers were submitted to the realization of Kolmogorov-Smirnov Test for Normality and compared among the evaluated ones by means of Friedman Test and correlated among themselves by means of the Spearman correlation, being the averages of roles and dominances compared by means of Mann-Whitney and Kruskal-Wallis/Dunn tests, affording the verification of differences found on managerial roles assumed by evangelical ministers as to their brain dominances and according to sociodemographic and functional differences. The ministers have demonstrated more willingness toward the mentor role, and presented dominance in the motive/relational brain Role. The statistic tests realized partially confirm the hypothesis that there is a correlation between brain dominances and managerial roles